Effectiveness Some Plant Extracts of Third Instar Nymphs Nezara viridula L. (Hemiptera: Pentatomidae) Attack on String Bean Pod - Cherin Manuputty; John A Patty; Saartje H Noya (Jurnal Agrosilvopasture-Tech, 2023)
The objective of this research wa to examine effectiveness of several plant extracts against of Thrid Instar Nymphs N. viridula on string bean pod. The experiment was conducted in the Laboratory of plant Pests, Faculty of Agriculture Pattimura University. The experimental method was a completely randomized design with five different treatments included A (garlic extract 15%), B (citronella extract 15%), C (neem leaf extract 15%), D (neem oil 2,5 %), E (Diazinon 600 EC 0,15%), and one control. Observations were made on the Early toxicity symptoms, cumulative mortality, and mortality rate of Thrid Instar Nymphs N. viridula The results showed that the application of garlic extract cumulative mortality 80%, mortality rate 5.11 hours kills 50% of test insects, citronella extract cumulative mortality 100%, mortality rate 0.98 hours kills 76.7% of test insects, neem leaf extract mortality cumulative 100% with a mortality rate of 0.86 hours, neem oil cumulative mortality of 66.67%, mortality rate of 9.72 hours killing 53.33% of test insects, and Diazinon 600 EC cumulative mortality of 100%, mortality rate of 0.80 hours killing 93.3%. Several plant extracts applied to Thrid Instar Nymphs N. viridula were very effective. Especially the treatment of neem leaves with a cumulative mortality of 100% with a mortality rate of 0.86 hours and citronella with a cumulative mortality of 100%, a mortality rate of 0.98 hours killed 76.7% of the test insects.